Determinants of capital structure of start-up firms in South Africa - Elomo, Pelagie Nadine (My University, 2015)
The capital structure of the firm is determined by several factors. An optimal capital structure leads the firm to achieve a better performance, ensures the sustainability in its operation and its viability. The objective of this study is to find out the relationship between capital structure determinants and leverage level of starts-up firms in South Africa. Cross-sectional OLS multiple regression analysis has been conducted on financial information contained in the pre-listing statement of firms to study the factors that affect the financial decisions of the non-financial starts-up companies; and to determine which capital structure determinant(s), among the many proposed in the literature, are relevant for them in the South Africa context. The final sample consists of 32 non-financial start-up companies. The dependent variable (leverage level of the companies), is measured by the short-term debt ratio, long-term debt ratio and total debt ratio. Independent variables (capital structure determinants) are measured by tangibility, profitability, firm size, firm risk, growth opportunity and age of the firm. We find that firm risk and firm growth opportunity have significant influence on the capital structure chosen by start-up firms in the South Africa context.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.